2019
DOI: 10.5230/jgc.2019.19.e43
|View full text |Cite
|
Sign up to set email alerts
|

LINC00703 Acts as a Tumor Suppressor via Regulating miR-181a/KLF6 Axis in Gastric Cancer

Abstract: Purpose: Long noncoding RNA 00703 (LINC00703) was found originating from a region downstream of Kruppel-like factor 6 (KLF6) gene, having 2 binding sites for miR-181a. Since KLF6 has been reported as a target of miR-181a in gastric cancer (GC), this study aims to investigate whether LINC00703 regulates the miR-181a/KLF6 axis and plays a functional role in GC pathogenesis. Materials and Methods: GC tissues, cell lines, and nude mice were included in this study. RNA binding protein immunoprecipitation (RIP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…[12][13][14] An increasing number of studies have shown that numerous lncRNAs are abnormally expressed in GC. [15][16][17] Notably, there is increasing evidence supporting a close relationship between lncRNA dysregulation and malignant characteristics in GC. 18,19 MicroRNAs (miRNAs, miRs) are classified as singlestranded noncoding short RNAs approximately 19-25 nucleotides in length.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] An increasing number of studies have shown that numerous lncRNAs are abnormally expressed in GC. [15][16][17] Notably, there is increasing evidence supporting a close relationship between lncRNA dysregulation and malignant characteristics in GC. 18,19 MicroRNAs (miRNAs, miRs) are classified as singlestranded noncoding short RNAs approximately 19-25 nucleotides in length.…”
Section: Introductionmentioning
confidence: 99%
“…For example, LINC00703/miR-181a/ KLF6 axis suppresses the development of gastric cancer. 25 LINC00312/miR-9/CDH1 axis was found to promote breast cancer progression. 26 Through bioinformatics, we found that miR-765 targeted NUTF2 in glioma.…”
Section: Dovepressmentioning
confidence: 99%
“…Recently, increasing research has revealed the crucial function of lncRNAs in tumorigenesis, including in GC ( 14 ). For instance, LINC00703 suppresses GC cell proliferation and invasion but induces apoptosis ( 15 ) and lncRNA GMAN promotes hepatocellular carcinoma progression by interacting with eIF4B ( 16 ). In the present study, according to the ENCORI database, SLCO4A1-AS1 expression was enhanced in GC samples compared with the normal samples.…”
Section: Discussionmentioning
confidence: 99%